The association between features of epicardial adipose tissue and the risks of early recurrence after catheter ablation in patients with atrial fibrillation - Feng, Leiyu; Li, Liming; Bai, Linpeng; Tang, Li; Zhao, Yintao; Zhao, Xiaoyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEpicardial adipose tissue (EAT) remodeling is associated with atrial fibrillation (AF). However, there is limited research on the contribution of EAT to the risk of AF recurrence (AFR). The purpose of this research was to assess the relationship between the risk of AFR after radiofrequency catheter ablation and the volume and attenuation of the EAT.MethodsWe included a total of 123 consecutive individuals who received AF ablation, 31 of whom suffered AFR. The volume and mean density of the whole-heart and periatrial EAT were measured on computed tomography images using four attenuation ranges. The clinical, atrial, and EAT characteristics of patients with and without AFR were compared. Logistic regression was used to identify independent risk factors and to build a model to predict recurrence. The relationship between EAT characteristics and recurrence was analyzed for the subtypes of AF.ResultsThe AFR group had a larger left atrial anteroposterior diameter (47.4 ± 7.4 vs. 43.7 ± 8.0 mm), left–right diameter (78.6 ± 7.9 vs. 74.7 ± 9.1 mm), and volume (145.9 vs. 127.0 mL) than the non-recurrence group (P = 0.021, 0.037, 0.015, respectively). The total EAT volume in the AFR group was significantly larger than that in the non-recurrence group, for both the overall and persistent AF groups (all P < 0.1). The periatrial EAT volume of the AFR group was significantly larger than that of the non-recurrence group for those with persistent AF (P = 0.047, 0.048, 0.048, 0.031 for four attenuation ranges). The total EAT volume and left atrial anteroposterior diameter were independent risk factors for AFR (P = 0.035, 0.045, respectively).ConclusionThe EAT volume and left atrial anteroposterior diameter were of great significance in predicting AFR.